COMPETITIVE ADSORPTION OF METAL CATIONS ONTO TWO GRAM POSITIVE BACTERIA: TESTING THE CHEMICAL EQUILIBRIUM MODEL - AN EXPERIMENTAL STUDY - Fowle D.A.; Fein J.B. (My University, 1999)
In order to test the ability of a surface complexation approach to account for metal-bacteria interactions in near surface fluid-rock systems, we have conducted experiments that measure the extent of adsorption in mixed metal, mixed bacteria systems. This study tests the surface complexation approach by comparing estimated extents of adsorption based on surface complexation modeling to those we observed in the experimental systems. The batch adsorption experiments involved Ca, Cd, Cu, and Pb adsorption onto the surfaces of 2 g positive bacteria: Bacillus subtilis and Bacillus licheniformis. Three types of experiments were performed: 1. Single metal (Ca, Cu, Pb) adsorption onto a mixture of B. licheniformis and B. subtilis; 2. mixed metal (Cd, Cu, and Pb; Ca and Cd) adsorption onto either B. subtilis or B. licheniformis; and 3. mixed or single metal adsorption onto B. subtilis and B. licheniformis. %Independent of the experimental results, and based on the site specific stability constants for Ca, Cd, Cu, and Pb interactions with the carboxyl and phosphate sites on B. licheniformis and B. subtilis determined by Fein et al. (1997), by Daughney et al. (1998) and in this study, we estimate the extent of adsorption that is expected in the above experimental systems.Competitive cation adsorption experiments in both single and double bacteria systems exhibit little adsorption at pH values less than 4. With increasing pH above 4.0, the extent of Ca, Cu, Pb and Cd adsorption also increases due to the increased deprotonation of bacterial surface functional groups. In all cases studied, the estimated adsorption behavior is in excellent agreement with the observations, with only slight differences that were within the uncertainties of the estimation and experimental procedures. Therefore, the results indicate that the use of chemical equilibrium modeling of aqueous metal adsorption onto bacterial surfaces yields accurate predictions of the distribution of metals in complex multicomponent systems.